An Efficient Synthesis, Evaluation of Parameters and Characterization of Nitro‐Hydroxyl‐Terminated Polybutadiene (Nitro‐HTPB). Issue 6 (15th May 2018) - Ghayeni, Hamid Reza; Razeghi, Reza; Olyaei, Abolfazl
Abstract: This article reports the nitration of Hydroxyl‐Terminated Polybutadiene (HTPB) backbone by facile and efficient "one pot" procedure, resulting in the formation of conjugated nitro‐alkene derivative of HTPB. The reaction was carried out with sodium nitrite and iodine. In order to optimization of the effective parameters on the synthesis of Nitro‐HTPB, the proportional amounts of reactant, amount of solvent and temperature were investigated and the effect of these parameters on the nitration double bond on HTPB backbone was evaluated. The product Nitro‐HTPB was characterized by FT‐IR, 1 H NMR and 13 C NMR spectroscopy as well as DSC, and TG. Abstract :